2017
DOI: 10.3892/or.2017.6142
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-505 is downregulated in human osteosarcoma and regulates cell proliferation, migration and invasion

Abstract: Recent studies have demonstrated that microRNAs (miRNAs/miRs) are involved in osteosarcoma tumorigenesis, progression, invasion and metastasis. For example, miR-505 plays important roles in human carcinogenesis; however, its exact function in osteosarcoma remains unclear. MicroRNA profiles of osteosarcoma and normal tissues were obtained by miRNA microarray assays, which were validated by quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR). Then, high-mobility group box 1 (HMGB1) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 41 publications
(39 reference statements)
1
35
0
Order By: Relevance
“…However, our understanding of how miRNAs regulate CC development and progression -particularly how they affect CC metastasis -remains limited. Recent studies demonstrate that microRNA-505 (miR-505) is dysregulated in different types of human cancers, including breast cancer, colorectal cancer, prostate cancer, endometrial cancer, bladder cancer, and hepatocellular carcinoma, among others [10][11][12][13][14][15][16][17][18][19][20][21][22]. Furthermore, miR-505 expression levels in plasma [21] and in whole blood [22] could be used as a potential non-invasive biomarker for bladder and pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, our understanding of how miRNAs regulate CC development and progression -particularly how they affect CC metastasis -remains limited. Recent studies demonstrate that microRNA-505 (miR-505) is dysregulated in different types of human cancers, including breast cancer, colorectal cancer, prostate cancer, endometrial cancer, bladder cancer, and hepatocellular carcinoma, among others [10][11][12][13][14][15][16][17][18][19][20][21][22]. Furthermore, miR-505 expression levels in plasma [21] and in whole blood [22] could be used as a potential non-invasive biomarker for bladder and pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are key regulators in the tumorigenesis of OS. Some miRNAs are down-regulated in OS, such as miR-133a, 24 -137, 25 -150, 26 -223, 27 -505, 28 and -564. 29 In consistent with these miRNAs, miR-431-5p was also down-regulated in OS tissues and cells in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated the significant down-regulation of miR-505 in HCC tissues compared with normal controls (data not shown). It has been found that miR-505 suppressed the proliferation, migration and invasion of osteosarcoma cells [15]. The potential tumor suppressive function of miR-505 was also demonstrated in cervical cancer and endometrial cancer [16,17].…”
Section: Introductionmentioning
confidence: 92%